Pengaruh Dimensi Servqual Terhadap Loyalitas Tamu Bossotel Inn, Bangkok Dengan Kepuasan Sebagai Variabel Intervening - Galuh Putri Manggali; Hary Sulaksono (JMBI : Jurnal Manajemen Bisnis dan Informatika, 2022)
This research aims to analyze servqual dimension that consisting of tangible, empathy, reliability, responsiveness, and assurance towards guest loyalty at Bossotel Inn, Bangkok, with satisfaction as an intervening variable. This research method uses quantitative descriptive research, data collection techniques using purposive sampling by distributing 100 questionnaires to the guest of Bossotel Inn, Bangkok, the analysis method used is path analysis using SPSS version 20 and the sobel test calculator to test hypotheses. The results of this research indicate that: 1) reliability and assurance variable have a direct effect on Bossotel Inn, Bangkok guest satisfaction. While tangible, empathy, and responsiveness variable do not have direct effect, 2) empathy and responsiveness variable have direct effect on Bossotel Inn, Bangkok guest loyalty, while tangible, reliability, and assurance variable have no effect, 3) hotel guest satisfaction variable has a direct effect on Bossotel Inn, Bangkok guest loyaltsy, and the last, 4) hotel guest satisfaction cannot be a mediate the relationship between tangible, empathy, reliability, responsiveness, and assurance towards guest loyalty at Bossotel Inn, Bangkok, Thailand.